Sintering behavior of nanocrystalline hydroxyapatite produced by wet chemical method - Ramesh, Singh; Tolouei, R.; Hamdi, M.; Purbolaksono, J.; Tan, C.Y.; Amiriyan, M.; Teng, W.D. (Bentham Science Publishers, 2011)
The sintering behavior of synthesized nanocrystalline hydroxyapatite (HA) powder was investigated in terms of phase stability and mechanical properties. A wet chemical precipitation method was successfully employed to synthesize a high purity and single phase HA powder. After shaping, HA powder compacts have been sintered over the temperature range of 1000 degrees C to 1300 degrees C. Two different sintering holding times of 1 minute and 120 minutes were investigated. The results revealed that the 1 minute holding time profile was effective in suppressing grain growth and producing a HA body with improved densification. Additionally, higher mechanical properties such as Young's modulus of 119 GPa, high fracture toughness of 1.41 MPa.m(1/2) and hardness of 9.5 GPa were obtained for this sample as compared to HA bodies when sintered using the 120 minutes holding time. The study revealed for the first time that HA could be sintered using a 1 minute holding time without compromising on HA phase stability and mechanical properties.